Characterization of the photo-detection efficiency temperature dependence of silicon photomultipliers from -30°C to 70°C. (1st December 2022) - Schmailzl, Wolfgang; Piemonte, Claudio; Schelhase, Stefan; Hansch, Walter
Abstract: We present photon detection efficiency (PDE) measurements of three different silicon photomultipliers (SiPM) and report the temperature coefficient of this parameter using a direct measurement method. This study provides first results in such a wide temperature and wavelength range, from -30°C to 70°C and from 365 nm to 900 nm respectively. To carry out this study we developed a setup providing stable illumination of the device under test in temperature. The PDE is evaluated using a photon-counting method and the wavelength-dependent PDE temperature coefficients of all devices are determined. The different designs are compared and the individual contributors to the temperature dependence of the PDE are discussed. The PDE is shown to be linearly dependent on temperature for all designs and the temperature coefficient depends on wavelength and bias voltage. At shorter wavelengths, the temperature dependency approaches values close to zero for one design whereas all devices show increasing temperature coefficients for increasing wavelengths. This study shows that despite the more complex designs of SiPMs, compared to silicon photodiodes, similar factors contribute to the temperature dependence of the PDE.